2004
DOI: 10.1111/j.1523-1739.2004.00152.x
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and Species Richness of Nocturnal Insects on Organic and Conventional Farms: Effects of Agricultural Intensification on Bat Foraging

Abstract: Insects are the principal food for many animals, including bats (Chiroptera), and all species of bats in the United Kingdom feed over agricultural habitats. Bat populations are declining throughout Europe, probably in part as a result of agricultural intensification. Organic farming prohibits the use of agrochemicals, a major component of agricultural intensification, making it an ideal control for a study of intensive agricultural systems. To evaluate the impact of agricultural intensification on bat foraging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
124
2
7

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(150 citation statements)
references
References 36 publications
(41 reference statements)
11
124
2
7
Order By: Relevance
“…This appears to be in contrast to other studies reporting insect abundances and diversity being negatively associated with agricultural intensification (e.g., Benton et al, 2002;Wickramasinghe et al, 2004). However, we compared abundance of nocturnal insects with more than 70% being Diptera.…”
Section: Food Availabilitycontrasting
confidence: 49%
“…This appears to be in contrast to other studies reporting insect abundances and diversity being negatively associated with agricultural intensification (e.g., Benton et al, 2002;Wickramasinghe et al, 2004). However, we compared abundance of nocturnal insects with more than 70% being Diptera.…”
Section: Food Availabilitycontrasting
confidence: 49%
“…Our findings differ from those of Bengtsson et al (2005) mainly in that predatory invertebrates only infrequently showed a significant response. Bats were not included in the meta-analysis of Bengtsson et al but Wickramasinghe et al (2004) have also suggested that organic farming is beneficial to bats, both through provision of more structured habitats and higher abundance of insect prey.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies targeted entire landscapes, comparing management impacts on insects over large scales (Bergman et al 2004;Wickramasinghe et al 2004). They typically relied on a few model groups, such as butterflies (Öckinger & Smith 2006;Rundlöf et al 2008), or bumblebees (Haaland & Gyllin 2010), although multi-taxa comparisons also exist (Meek et al 2002;Roth et al 2008;Sjodin et al 2008;Čížek et al 2012).…”
Section: Introductionmentioning
confidence: 99%